Chapter 6 Ion Implantation - Langouche G.; Yoshida Y. (Springer, 2013)
In this tutorial we describe the basic principles of the ion implantation technique and we demonstrate that emission Mössbauer spectroscopy is an extremely powerful technique to investigate the atomic and electronic conﬁguration around implanted atoms. The physics of dilute atoms in materials, the ﬁnal lattice sites and their chemical state as well as diffusion phenomena can be studied. We focus on the latest developments of implantation Mössbauer spectroscopy, where three accelerator facilities, i.e., Hahn-Meitner Institute Berlin, ISOLDE-CERN and RIKEN, have intensively been used for materials research in in-beam and on-line Mössbauer experiments immediately after implantation of the nuclear probes.
Keywords: implantation technique; emission Mössbauer spectroscopy